ANALISIS TEKNOLOGI PENGOLAHAN LIMBAH CAIR PADA INDUSTRI TEKSTIL (STUDI KASUS PT. ISKANDAR INDAH PRINTING TEXTILE SURAKARTA) - Junaidi, Junaidi (Universitas Diponegoro, 2006)
Industrial activities which grow rapidly caused contamination of environment generated by throwing away industrial disposal. PT. IskandarIndah Printing Textile as one of the textile factory at Surakarta managed their waste water by processing it used waste water treatment plant, so that fulfilled quality standard. Characteristic waste water divided to become physics characteristic, chemical, and biological. Unit processing of waste consist of unit operate and unit process. Operation unit consist of ekualisasi, koagulasi, flokulasi, sedimentation, and aerasi. While for the unit of process cover processing of biology and processing of chemistry.Waste water treatment plant at PT. Iskandar Indah Printing Textille Surakarta consist of unit of ekualisasi, koagulasi, flokulasi, primary sedimentation, netralisasi, biological basin, secondary sedimentation, rapid sand filter, and sludge drying bed. Quality efluent of waste water treatment plant, measured to pass efluen sand filter, because this unit represent last unit.